Reengineering the electrical wiring system of Cebu Technological University, Tuburan Campus / Romel D. Baflor, Alden Q. Gabuya, Jr. and Gregorion P. Pajaron Jr. - Baflor, Romel D.; Gabuya Jr., Alden Q.; Pajaron Jr., Gregorion P. (UiTM Press, 2024)
This study aimed to assess the condition of the electrical wiring system at Cebu Technological University (CTU) during the fiscal year 2019-2020, serving as the basis for proposing a cost-effective electrical wiring system. The research was conducted specifically at CTU-Tuburan Campus (CTU-TC), utilizing the energy audit and descriptive research methods. To gather the necessary data for analysis, an inventory of electrical loads, electrical wirings, and circuit breakers was conducted. Electrical engineering computations were performed to calculate relevant data related to capacity, cost savings, and safety during the inventory process. The findings revealed that the existing electrical conductors and circuit breakers were inadequate to handle the total load of 483.285 kilowatts. Consequently, it was concluded that the current electrical wiring system at CTU-Tuburan is neither cost-effective nor safe, and it lacks the capacity to accommodate the existing electrical loads. Therefore, it is strongly recommended to implement a proposed electrical wiring system alongside a regular maintenance program. The proposed electrical wiring system aims to address the identified shortcomings by ensuring cost-effectiveness, safety, and improved capacity to handle the electrical loads. The regular maintenance program will help maintain the system's functionality and longevity, ensuring its sustained effectiveness. Implementing these recommendations will result in an optimized electrical infrastructure for CTU-Tuburan, supporting the efficient and safe operation of its electrical systems.